FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PT BUKAKA TEKNIK UTAMA BALIKPAPAN - Hardiyono, Hardiyono; Yuliana, Lina; Subaktiar, Arief (IDENTIFIKASI, 2021)
This study aims to determine the effect of any influences that affect worker compliance with the use of personal protective equipment on fabricated workers at PT . Unlock the Main Techniques of Balikpapan. The sampling technique was carried out by total sampling which then selected 35 workers from the established criteria as samples. The results of the study using multiple regression showed that knowledge of workers, comfort of PPE and supervision of workers had a positive influence on the use of personal protective equipment. Worker knowledge has a significant positive effect on the use of PPE with t count > t table, namely 4.579> 2.039 or sig.t value (0.124) < = 0.5 . Meanwhile, the availability and comfort of workers were also found to have a positive effect on profitability with t count < t table, namely 1.197 < 2.039 or sig.t (0.03) < = 0.5. Likewise, the worker supervision factor also has a positive effect on profitability with t count < t table that is 3.903> 2.039 or sig.t value (0.066) < = 0.5